2012
DOI: 10.14260/jemds/134
|View full text |Cite
|
Sign up to set email alerts
|

Pap Smear for Screening T. Vaginalis

Abstract: BACKGROUND: Trichomonas vaginalis is sometimes seen in Papanicolaou stained smears, but because emphasis is placed on malignant cells in Papanicolaou stained smears, not much is done to search for this parasite in smears. In this study, cervical and vaginal specimens were examined by conventional Papanicolaou method for the presence of Trichomonas vaginalis microscopically. MATERIALS AND METHODS: Five hundred high vaginal swabs collected from gynaecology OPD were stained with Papanicolaou stain. RESULTS: One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…In TV infected patients, the symptoms range widely from vaginal discharge and pruritis to dysuria and dyspareunia. 18 The present study matwith this clinical profile. The classical green, frothy, foul-smelling discharge was documented in 10% of patients.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In TV infected patients, the symptoms range widely from vaginal discharge and pruritis to dysuria and dyspareunia. 18 The present study matwith this clinical profile. The classical green, frothy, foul-smelling discharge was documented in 10% of patients.…”
Section: Discussionmentioning
confidence: 51%
“…19 In the present study, the prevalence of Trichomonas infection is 5.07% which is similar to other studies. 18,19 Herpes simplex Virus (HSV) is one of the sexually transmitted infections and is a rare cause of abnormal Pap smears as observed in the present study. The cytological diagnosis of genital herpes depends upon the recognition of multinucleated giant squamous cells in Papanicolaou-stained smears.…”
Section: Discussionmentioning
confidence: 53%
“…Our study correlates well with the finding of studies done by Bukhari et al 1 and Cheraghi et al 3 where TV was the reason for symptomatic and asymptomatic infection related to female urogenital system. A study conducted by De Glehn et al 13 also identified the high prevalence of TV infection among the samples studied and the infection was positively associated with the number of life time sex partners.Similarly, Malkappa et al 14 and Brooks-Smith-lowe et al 15 also reported the higher incidence of TV infection.…”
Section: Discussionmentioning
confidence: 83%